Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.